Strategi Pemberdayaan Masyarakat melalui Pengelolaan Balai Ekonomi Desa (Balkondes) Wringinputih, Borobudur, Magelang, Jawa Tengah - Rahadiyand Aditya; Suyanto Suyanto (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
This study looks at the empowerment strategy carried out by the Wringinputih Village Economic Center (Balkondes). The research method used is descriptive qualitative method with data collection techniques using interviews, observation and documentation studies. The results of this study indicate that the strategy carried out by Balkondes Wringinputih is in the form of awareness transformation, capacity building, and capacity building. These three things have been done. Transformation of awareness by involving the community in various events. Capacity building by involving the community in training and capacity building events by providing opportunities for the community to provide opinions. Balkondes is also used as a display case for local wisdom in Wringinputih Village, besides that, it is also used as a place to promote the village's superior products.